Effects of 3 Weeks of Oral Low-Dose Cobalt on Hemoglobin Mass and Aerobic Performance - Hoffmeister, Torben; Schwenke, Dirk; Krug, Oliver; Wachsmuth, Nadine; Geyer, Hans; Thevis, Mario; Byrnes, William C.; Schmidt, Walter F. J. (Frontiers in Physiology, 2018)
Introduction: Cobalt ions (Co2+) stabilize HIFα and increase endogenous erythropoietin (EPO) production creating the possibility that Co2+ supplements (CoSupp) may be used as performance enhancing substances. The aim of this study was to determine the effects of a small oral dosage of CoSupp on hemoglobin mass (Hbmass) and performance with the objective of providing the basis for establishing upper threshold limits of urine [Co2+] to detect CoSupp misuse in sport. Methods: Twenty-four male subjects participated in a double-blind placebo-controlled study. Sixteen received an oral dose of 5 mg of ionized Co2+ per day for three weeks, and eight served as controls. Blood and urine samples were taken before the study, during the study and up to 3 weeks after CoSupp. Hbmass was determined by the CO-rebreathing method at regular time intervals, and VO2max was determined before and after the CoSupp administration period. Results: In the Co2+ group, Hbmass increased by 2.0 ±2.1% (p<0.001) while all the other analyzed hematological parameters did not show significant interactions of time and treatment. Hemoglobin concentration ([Hb]) and hematocrit (Hct) tended to increase (p=0.16, p=0.1) and also [EPO] showed a similar trend (baseline: 9.5 ±3.0, after two weeks: 12.4 ±5.2 mU/ml). While mean VO2max did not change, there was a trend for a positive relationship between changes in Hbmass and changes in VO2max immediately after CoSupp (r=0.40, p=0.11). Urine [Co2+] increased from 0.4 ±0.3 ng/ml to 471.4 ±384.1 ng/ml (p<0.01) and remained significantly elevated until two weeks after cessation. Conclusion: An oral Co2+ dosage of 5 mg/day for three weeks effectively increases Hbmass with a tendency to increase hemoglobin concentration ([Hb]) and hematocrit (Hct). Because urine Co2+ concentration remains increased for two weeks after cessation, upper limit threshold values for monitoring CoSupp can be established.